Eukaryotic translation initiation factor 3 (eIF3) subunit e is essential for embryonic development and cell proliferation - Sadato, Daichi (FEBS Open Bio, 2018)
Mammalian eukaryotic translation initiation factor 3 (eIF3) is the largest complex of the translation initiation factors. The eIF3 complex is comprised of thirteen subunits, which are named eIF3a to eIF3 m in most multicellular organisms. The eIF3e gene locus is one of the most frequent integration sites of mouse mammary tumor virus (MMTV), which induces mammary tumors in mice. MMTV‐integration events result in the expression of C‐terminal‐truncated eIF3e proteins, leading to mammary tumor formation. We have shown that tumor formation can be partly caused by activation of hypoxia‐inducible factor 2α. To investigate the function of eIF3e in mammals, we generated eIF3e‐deficient mice. These eIF3e (−/−) mice are embryonically lethal, while eIF3e (+/−) mice are much smaller than wild‐type mice. In addition, eIF3e (+/−) mouse embryonic fibroblasts (MEFs) contained reduced levels of eIF3a and eIF3c subunits and exhibited reduced cellular proliferation. These results suggest that eIF3e is essential for embryonic development in mice and plays a role in maintaining eIF3 integrity.